Technical architecture and strategies for intelligent construction of coal preparation plant - WANG Meijun; TAN Zhanglu; LÜ Hanbing; GUI Yudian (矿业科学学报)
Intelligentization of coal preparation plant is the core technical support for the high-quality development of coal washing. This study targets at the top-level design for the intelligent construction of coal preparation plant. Departing from the fundamental purpose and motivation of digital transformation of coal preparation plant, we 1) discuss the technical objectives and major tasks of intelligent construction of coal preparation plant based on the underlying logic of intelligent construction of coal preparation plant; 2) propose the overall technical architecture of CNSASSM for the intelligent construction of coal preparation plant based on layered architecture, with five core competence requirements: "thorough perception, deep interconnection, autonomous learning, intelligent application, and global coordination"; 3) point out the technical pathway for intelligent construction of coal preparation plant and the major tasks to be completed at each phase based on capability maturity, including the integration of standard coal preparation data at the primary phase, the research and development of business optimization algorithms at the intermediate phase, and the empowerment of artificial intelligence model on coal preparation at the advanced phase; 4) generalize a 96-word guideline of technical strategies for intelligent construction of coal preparation plant based on patterns of complex system development, so as to provide reference for the technical realization of intelligent construction of coal preparation plant from the perspective of top-level design.